Oxford Handbooks Online 2011
DOI: 10.1093/oxfordhb/9780199580583.003.0022
|View full text |Cite
|
Sign up to set email alerts
|

A Review of the IT Outsourcing Literature: Insights for Practice

Abstract: We now differentiate between the requirements for new and revised submissions. You may choose to submit your manuscript as a single Word or PDF file to be used in the refereeing process. Only when your paper is at the revision stage, will you be requested to put your paper in to a 'correct format' for acceptance and provide the items required for the publication of your article. To find out more, please visit the Preparation section below. Article structure Subdivision-unnumbered sections Divide your article i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
165
0
17

Year Published

2011
2011
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 115 publications
(186 citation statements)
references
References 0 publications
4
165
0
17
Order By: Relevance
“…Backward search (14 relevant articles) and forward search (14 relevant articles) were conducted subsequently. Additionally, we conducted a backward search on selected CC and ITO literature reviews (Lacity et al, 2009;Martens and Teuteberg, 2009;Lacity et al, 2010Lacity et al, , 2011Venters and Whitley, 2012;Yang and Tate, 2012) and identified 12 additional relevant articles. Thus, the total set of articles considered in this literature review includes 88 articles that have been published before April 2014…”
Section: Private Sectormentioning
confidence: 99%
“…Backward search (14 relevant articles) and forward search (14 relevant articles) were conducted subsequently. Additionally, we conducted a backward search on selected CC and ITO literature reviews (Lacity et al, 2009;Martens and Teuteberg, 2009;Lacity et al, 2010Lacity et al, , 2011Venters and Whitley, 2012;Yang and Tate, 2012) and identified 12 additional relevant articles. Thus, the total set of articles considered in this literature review includes 88 articles that have been published before April 2014…”
Section: Private Sectormentioning
confidence: 99%
“…8 We attempted additional controls including industry, country and size of the company, but none of them had a significant effect on the outcomes; in order to avoid over-saturating the regression model we do not include them in further analysis. 9 In line with IS outsourcing literature, we have distinguished between IT and business process outsourcing (Lacity et al 2011, Lacity et al 2009Mani et al 2010). IT outsourcing (ITO) is defined as the sourcing of Information Technology services through an external third party (Lacity et al 2011).…”
Section: Control Variablesmentioning
confidence: 99%
“…Technology is approaching the stage of creation and outsourcing of sustainable IT businesses based on the principles of green economics. Unparalleled progress in the demand for IT facilities and outsourcing has led to the expansion of large, complex, resource-exhaustive infrastructure called server farms to support business needs [4].The data center industry has emerged as a significant corporate asset, playing a vital role in business management by serving as nerve cells of any information society and IT business [5]. These facilities assimilate and store large amounts of information and process all activities and services that require Information Communication Technology (ICT) equipment, cooling and power delivery equipment, servers and storage devices to store, process, and exchange digital information [6].…”
Section: Introductionmentioning
confidence: 99%
“…Globally, the total electrical power consumption by data centers, servers, and computers is steadily increasing [4]. This increase leads to the emission of greenhouse gases that exacerbate global warming and pose risks to environmental health.…”
Section: Introductionmentioning
confidence: 99%